Quantitative ultrasound and dual-energy x ray absorptiometry in bone status assessment of ex-preterm infants. Issue 2 (15th June 2007) - Gianni, M L; Mora, S; Roggero, P; Mosca, F
Abstract : Preterm infants are at increased risk of low bone mass. Quantitative ultrasound (QUS) is a non-invasive method for assessment of bone status. The application of QUS in a cohort of ex-preterm infants was investigated. This study suggests that QUS cannot be used as a surrogate for dual-energy x ray absorptiometry.